Serum of patients with active rheumatoid arthritis inhibits differentiation of osteochondrogenic precursor cells. (3rd May 2016) - Pathak, Janak L.; Verschueren, Patrick; Lems, Willem F.; Bravenboer, Nathalie; Klein-Nulend, Jenneke; Bakker, Astrid D.; Luyten, Frank P.
ABSTRACT: Delayed fracture healing is frequently experienced in patients with systemic inflammation such as during rheumatoid arthritis (RA). The reasons for this are diverse, but could also be caused by inflammatory cytokines and/or growth factors in serum from patients with active disease. We hypothesized that serum from patients with active RA contains circulating inflammatory factors that inhibit differentiation of osteochondrogenic precursors. Serum was obtained from 15 patients with active RA (active RA-sera) and from the same patients in clinical remission 1 year later (remission RA-sera; controls). The effect of active RA-sera on osteochondrogenic differentiation of chondrogenic ATDC5 cells and primary human periosteum–derived progenitor cells (HPDC) was determined in micromass culture. In ATDC5 cells, active RA-sera reduced Ki67 transcription levels by 40% and cartilage matrix accumulation by 14% at day 14, and Alp transcription levels by 16%, and matrix mineralization by 17% at day 21 compared with remission RA-sera. In HPDCs, active RA-sera inhibited metabolic activity by 8%, SOX9 transcription levels by 14%, and cartilage matrix accumulation by 7% at day 7 compared with remission RA-sera. In conclusion, sera from patients with active RA negatively affect differentiation of osteochondrogenic precursors, and as a consequence may contribute to delayed fracture healing in these patients.